Pengaruh Zinc Chitosan Cream terhadap Proses Penyembuhan Ulkus Diabetikum pada Pasien Diabetes Mellitus Tipe II - Tambunan, Sulastri G P; Parlaungan, Jansen (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this study was to analyze the healing process of diabetic ulcers in Type II Diabetes Mellitus patients on day 1, day 7 and day 14 at the Asri Wound Care Center Medan clinic. The research method used is Quasi Experimental research using a one group pretest-posttest design. The intervention used is Zinc Chitosan Cream. The tests used are the Kruskal Wallis Test and the Wilcoxon Test. The research results show that the Sig. (2-tailed) day 1 to day 7 for an Asymp Sig value of 0.000 < 0.05 there is a significant difference, day 7 to day 14 for an Asymp Sig value of 0.157 < 0.05 there is no significant difference, day 1 to day for the 14th Asymp Sig value of 0.000 < 0.05, there is a significant difference, it can be concluded that the effect of Zinc Chitosan Cream on healing diabetic ulcers in Type II Diabetes Mellitus patients only affects days 1 - 7 and day 1 - 14, whereas for days 7 – day 14 in healing diabetic ulcers in patients with Type II Diabetes Mellitus does not affect the wound healing process. In conclusion, Zinc Chitosan Cream in healing diabetic ulcers in Type II Diabetes Mellitus patients only has an effect on days 1 - 7 and days 1 - 14. Keywords: Type II Diabetes Mellitus, Diabetic Ulcers, Zinc Chitosan Cream.